The American dream in the 21st century - Hanson, Sandra L.; White, John Kenneth, 1952- (Temple University Press, 2011)
The American Dream has long been a dominant theme in U.S. culture, one with enduring significance, but these are difficult times for dreamers. The editors of and contributors to The American Dream in the 21st Century examine the American Dream historically, socially, and economically and consider its intersection with politics, religion, race, gender, and generation. The conclusions presented in this short, readable volume provide both optimism for the faith that most Americans have in the possibility of achieving the American Dream and a realistic assessment of the cracks in the dream. The las.